INOVASI ARTISTIK DAN APPROPRIASI KULTURAL SENI PERTUNJUKAN TRADISI TERHADAP BUDAYA GLOBAL - Isa Ansari (Institut Seni Indonesia Surakarta, 2015)
This paper aims to analyze the relationship between tradition and contemporary conditions,especially with the implementation of the AEC (Asean Economic Community). The problems ishow-cultural trendconducted by the local communities related to the interaction with the globalculture in the context of art.Usingcultural adaptation concept on the ecological anthropologyperspective. This approach is theorized that the process of adaptation is an active humansaction by using the power of reason while physically works in order to take advantage of thenatural resources. From visual observation of the socio-cultural phenomenonand a review ofseveral books, the research result at least there are some propensity adaptations made bytraditional artists, artistic innovation, cultural appropriation, and cultural delocalization.Keywords: Artistic inovation, cultural-appropriation, delocalization.